Digital Quran applications on smart phones and tablets: A study of the foundation programme students - Engku Ahmad Zaki, Engku Alwi; Norazmi, Anas; Mohd. Syahril, Ibrahim (Canadian Center of Science and Education, 2014)
This study aimed to investigate the students’ interest level and tendency towards reciting Quran using smart phones and tablets amongst 230 Muslim students of Foundation Programme at UiTM Kuantan Campus, Malaysia semester 2012/2013. The main instrument utilized in this study was a questionnaire while data analysis was accomplished using descriptive statistics of SPSS version 20. Based on the analysis, it was indicated that the students’ interest of reciting Quran was at a good level. However, 32.6% to 53.0% of them were not really sure about the rules involved when using digital Quran applications stored on the devices. These were among the primary concerns of the present study. Therefore, issues related to Islamic jurisprudence were clarified so that the students would become aware to take necessary steps in compliance with the religious laws when using such devices.